Perkembangan Legal Standing dalam Hukum Lingkungan (Suatu Analisis Yuridis dalam Public Participatory untuk Perlindungan Lingkungan) - Nommy H.T. Siahaan (Fakultas Hukum, Universitas Islam Bandung, 2011)
The environmental management policies are not rarely accused by various parties, related to the objective fact that when the most susceptible to suffer are the lower circles of society, let’s say the farmers, the rural community, or the inhabitants of the land which has potential value of natural resources. Those circles of society often have no idea about the threats that are coming upon them related to the development impacts and the environmental management, and when they suffer loss, they can do nothing about it. Many countries, especially the Common Law countries have accommodated some environmental law policies that are massive interest oriented, such as class action, legal standing, citizen lawsuit or also called as citizen standing, because by such system it will give so much ease to the victims or the plaintiffs to do lawsuits based on the loss they suffer caused by other parties. But unfortunately, about citizen lawsuit, until now it hasn’t been a part of the national legislation because it is not regulated in the constitution. Whereas, in the era before Acts Number 32 Year 1999 was put into effect, in the practice there had been several times that a citizen lawsuit had been submitted to the courts in Indonesia, some of which had been approved and had become permanent jurisdictions.